Optimal allocation of distributed generation for improving chargeability and voltage profile under different operative scenarios (2018)
ABSTRACT: This paper presents an application of a GRASP metaheuristic for the optimal allocation of distributed generation (DG) in electric power systems. Four indexes indicating the system performance in normal operation and under contingency were designed to guide the search. The proposed indexes indicate violations in chargeability and voltage limits for different operative scenarios. The objective function consists on minimizing the impacts of single contingencies in the chargeability and voltage profile of a network. To show the applicability and effectiveness of the proposed approach several tests were performed on the IEEE 30 and 57 bus tests systems. Results show that the proposed approach allows to find the allocation of DG that maximizes its positive impacts in terms of voltage profile and chargeability.